ORIGIN AND SPREAD OF CUTANEOUS AND MUCOSAL LEISHMANIASIS IN ANDEAN-AMAZONIAN - Altamirano Enciso, Alfredo J. (2014)
Drawing from four sixteenth-century sources, the article reports some apparent incidents of American Tegumentary Leishmaniasis within the territory of the Andes. Reinterpretation of these sources affords a look at the longstanding issue of the origin of espundia, or mucosal Leishmaniasis (ML). The study reinforces the hypothesis that ML originated in the western Amazon region, from there climbing into the high forests and later into hot inter-Andean lands via Bolivia’s and Peru’s borders with Brazil, above all through human migration. Dating to archeological times, this process intensified during the Inca period under the social policies of the mitmaq or mitimaes. These events transpired within the historical and social context of the fall of the Inca Empire and the advent of Spanish colonization.